Strategi Pondok Pesantren dalam Meningkatkan Kemampuan Santri Berfikir Kritis Terhadap Perkembangan Media Sosial : Studi Kasus di Pondok Pesantren Daruttaqwa III Gresik - Ahmad Zaky Azkyak; H. Mustadi (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
In the current digital era, social media has become an open space filled with streams of information, including invalid ones. Santri, as the future generation of the ummah, are required to have critical thinking skills to filter, analyze, and make wise decisions. Islamic boarding schools as traditional Islamic educational institutions are faced with the challenge to remain relevant amidst technological developments. This study aims to: 1) Find out the strategies of Pondok Pesantren Daruttaqwa III Gresik in improving students’ critical thinking skills toward social media developments, 2) Identify supporting and inhibiting factors in the implementation of the strategy, 3) Understand the role of Pondok Pesantren Daruttaqwa III in integrating traditional values with modern approaches to sharpen students’ critical thinking skills. This research uses a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation. The data analysis includes data collection, data reduction, data presentation, and drawing conclusions. The results show that the strategies include: 1) Integration of digital literacy and critical thinking in the formal education curriculum, 2) Character building and supervision in the dormitory environment as a key strategy, 3) Strengthening through extracurricular activities, awareness campaigns, and limited training. Supporting factors include strong leadership, dedication from teachers and administrators, presence of traditional Islamic values as ethical foundations, and increased student awareness. Obstacles include time limitations, lack of structured materials, varying digital literacy levels, and the rapid evolution of social media. The pesantren has successfully integrated Islamic values such as tabayyun, adab, amanah, and husnudzon with modern approaches.